Book Review: Inspiration and Innovation in Teaching and Teacher Education - Brenna, Beverley Anne (Journal of the Canadian Association for Curriculum Studies, 2016)
Inspiration and Innovation in Teaching and Teacher Education is an edited book by Karen Goodnough, Gerald Galway, Cecile Badenhorst, and Rob Kelly (2013) presenting a collection of 13 chapters, with three overview chapters in sections titled: “The Essence of Teacher Education”, “Innovative Practices in Teacher Education”, and “Emerging Issues in Teacher Education”. The book serves to remind readers of the history of teacher education as a landscape for new and future endeavors in the field, and it offers current research to address provocative questions related to a profession whose first responsibilities are presented as both political, in terms of the future of democracy, and personal, in terms of students who demonstrate particular values such as a sense of responsibility for themselves, others and the land through sustainability, as well as the skills to live those values. This text is a comprehensive and contemporary read and, as such, is highly recommended for Canadian curriculum scholars and students as well as others interested in the field of Education.